2017
DOI: 10.1021/acs.jcim.6b00646
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Principal Component Modes from Molecular Dynamics Simulations of Proteins

Abstract: Principal component analysis is a technique widely used for studying the movements of proteins using data collected from molecular dynamics simulations. In spite of its extensive use, the technique has a serious drawback: equivalent simulations do not afford the same PC-modes. In this article, we show that concatenating equivalent trajectories and calculating the PC-modes from the concatenated one significantly enhances the reproducibility of the results. Moreover, the consistency of the modes can be systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Hence, dynamics-based network analysis is presently one of the most comprehensive tools used to explore allosteric modulation of kinases. MD simulations provide a robust dataset for all-atomic fluctuations that can be analyzed for allosteric dynamics (33)(34)(35). Two key issues were kept in mind while searching for functionally relevant networks of correlated motions in our unbiased simulations: (i) that network analysis is dependent on the length of the simulation trajectory (36), wherein the description of conformational ensembles must adequately sample the free-energy landscape of the desired allosteric process; (ii) that it is more relevant to understand these inner amino acid motions in the context of experimentally verifiable observables that can corroborate the role of said dynamics in the kinase structure-function relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, dynamics-based network analysis is presently one of the most comprehensive tools used to explore allosteric modulation of kinases. MD simulations provide a robust dataset for all-atomic fluctuations that can be analyzed for allosteric dynamics (33)(34)(35). Two key issues were kept in mind while searching for functionally relevant networks of correlated motions in our unbiased simulations: (i) that network analysis is dependent on the length of the simulation trajectory (36), wherein the description of conformational ensembles must adequately sample the free-energy landscape of the desired allosteric process; (ii) that it is more relevant to understand these inner amino acid motions in the context of experimentally verifiable observables that can corroborate the role of said dynamics in the kinase structure-function relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Variance-covariance matrices were calculated for the Cα atoms of the TM domain, including D358 to C646, after a RMSD fitting of the receptor conformation at time t on top of the conformation at time 0, for time frames taken every 4 ps for trajectories R0-2 [55]. Principal component analysis (PCA) was performed in order to summarize the main fluctuations using the first principal component axis [56].…”
Section: Methodsmentioning
confidence: 99%
“…Ref. [36] introduced and examined a parameter that evaluates the overlap between such subspaces, called the root mean squared inner product (RMSIP), and suggested that PCA for the concatenated equivalent trajectories achieves better reproducibility.…”
Section: Error In Pcamentioning
confidence: 99%